Surface characteristics and fatigue behavior of shot peened Inconel 718 - Klotz, T.; Delbergue, D.; Bocher, P.; Lévesque, M.; Brochu, M. (International journal of fatigue, 2018)
[Display omitted] •Shot peening has a detrimental effect on fatigue life in low cycle fatigue.•Shot peening can increase fatigue life from two to twenty times in HCF.•The presence of significant residual stresses is the controlling factor in HCF.•Shot peening induced residual stresses mainly redistribute during the first cycle.•In HCF, a subsurface tensile residual stress peak promotes crack nucleation. Shot peening is commonly used in the aerospace industry to improve mechanical components fatigue life. It introduces compressive residual stresses and cold work at the surface which tend to close short fatigue cracks and delay their propagation, respectively. However, shot peening also creates surface irregularities that can be detrimental to fatigue. The effect of different shot peening conditions on Inconel 718 tested in low and high cycle fatigue is presented in this study. An analysis of the fatigue life, crack initiation mechanisms, residual stress relaxation, process induced strain hardening and surface roughness showed that, in high cycle fatigue, shot peening can increase Inconel 718 fatigue life from 2 to 20 times, depending on the shot peening conditions. This observation suggests that careful selection of peening parameters is crucial. In low cycle fatigue the roughness resulting from shot peening is to be considered while in high cycle fatigue, it is the presence of significant residual stresses.